A Cross-sectional Survey of the North American Skull Base Society on Vestibular Schwannoma, Part 2: Perioperative Practice Patterns of Vestibular Schwannoma in North America - Van Gompel, Jamie J.; Carlson, Matthew L.; Wiet, R. Mark; Tombers, Nicole M.; Devaiah M, Anand K.; Lal, Devyani; Morcos, Jacques J.; Link, Michael J. (Journal of Neurological Surgery Part B: Skull Base, 2018)
Introduction Perioperative care of vestibular schwannoma (VS) patients is extremely variable across surgeons and institutions making practice patterns difficult to standardize. No data currently exist detailing this practice variability.Methods The North American Skull Base Society membership was electronically surveyed regarding perioperative care of surgically operated VS patients.Results There were 87 respondents to the survey. Surgical positioning, surgical approach utilized, and perioperative medical adjuncts are quite variable. However, of those performing retrosigmoid approaches, 49% perform this in the supine position, while 33% use a park-bench position with only 2% using the sitting position. In those performing translabyrinthine approaches, 86% perform this in supine position. Although the use of neuromonitoring appears to be standard of care (98%), other than the seventh nerve, there is substantial variability between respondents regarding monitoring of additional cranial nerves. Postoperative antibiotics are used by 65%, postoperative steroids 81%, and postoperative chemical deep vein thrombosis prophylaxis in 68% of survey respondents.Conclusion Although the perioperative adjuncts to VS surgery are variable, there does appear to be a trend in common practice. Therefore, making surgeons aware of these trends may lead to standardized practice or alternatively trials of these variances to instruct which truly improve patient outcomes.
Keywords: vestibular schwannoma; skull base; cranial; microsurgical